Metoclopramide Improves the Quality of Tramadol PCA Indistinguishable to Morphine PCA: A Prospective, Randomized, Double Blind Clinical Comparison. Issue 9 (21st June 2013) - Pang, Weiwu; Liu, Yu‐Cheng; Maboudou, Edgard; Chen, Tom XianXiu; Chois, John M.; Liao, Cheng‐Chun; Wu, Rick Sai‐Chuen
Abstract Objective Multimodal analgesia has been effectively used in postoperative pain control. Tramadol can be considered "multimodal" because it has two main mechanisms of action, an opioid agonist and a reuptake inhibitor of norepinephrine and serotonin. Tramadol is not as commonly used as morphine due to the increased incidence of postoperative nausea and vomiting (PONV). As metoclopramide is an antiemetic and an analgesic, it was hypothesized that when added to reduce PONV, metoclopromide may enhance the multimodal feature of tramadol by the analgesic property of metoclopramide. Therefore, the effectiveness of postoperative patient‐controlled analgesia (PCA) with morphine was compared against PCA with combination of tramadol and metoclopramide. Design A prospective, randomized, double blind clinical trial. Setting Academic pain service of a university hospital. Subjects Sixty patients undergoing elective total knee arthroplasty with general anesthesia. Methods Sixty patients were randomly divided into Group M and Group T. In a double‐blinded fashion, Group M received intraoperative 0.2 mg/kg morphine and postoperative PCA with 1 mg morphine per bolus, whereas Group T received intraoperative tramadol 2.5 mg/kg and postoperative PCA with 20 mg tramadol plus 1 mg metoclopramide per bolus. Lockout interval was 5 minutes in both groups. Pain scale, satisfaction rate, analgesic consumption, PCA demand, and side effects were recorded by a blind investigator. Results These two groups displayed no statistically significant difference between the items and variables evaluated. Conclusions This combination provides analgesia equivalent to that of morphine and can be used as an alternative to morphine PCA.